Vitamin A Supplementation as an Intervention for Reducing Stunting in Young Children in Coastal Regions of Indonesia - Listy Handayani; Muhammad Amin; Wartina Karamelka (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Stunting is a manifestation of impaired growth and development in children, primarily caused by chronic malnutrition, recurrent infections, and insufficient psychosocial stimulation. Vitamin A deficiency is recognized as a major contributing factor to stunting due to its critical role in supporting immune function and enhancing resistance to infections. Although global initiatives have aimed to combat vitamin A deficiency, its specific impact on reducing stunting particularly in coastal regions with limited access to nutritious food and healthcare remains insufficiently examined. Objective: This study aims to analyze the role of vitamin A supplementation as a public health intervention for reducing stunting in young children, with a particular focus on coastal areas where nutritional and healthcare challenges are more prevalent. Methods: This study utilized a systematic literature review methodology, employing the keywords